Beyond barrier functions: Roles of pericytes in homeostasis and regulation of neuroinflammation. Issue 12 (20th August 2020) - Bhattacharya, Anindita; Kaushik, Deepak Kumar; Lozinski, Brian Mark; Yong, V. Wee
Abstract: Pericytes are contractile cells that extend along the vasculature to mediate key homeostatic functions of endothelial barriers within the body. In the central nervous system (CNS), pericytes are important contributors to the structure and function of the neurovascular unit, which includes endothelial cells, astrocytes and neurons. The understanding of pericytes has been marred by an inability to accurately distinguish pericytes from other stromal cells with similar expression of identifying markers. Evidence is now growing in favor of pericytes being actively involved in both CNS homeostasis and pathology of neurological diseases, including multiple sclerosis, spinal cord injury, and Alzheimer's disease among others. In this review, we discuss the current understanding on the characterization of pericytes, their roles in maintaining the integrity of the blood–brain barrier, and their contributions to neuroinflammation and neurorepair. Owing to its plethora of surface receptors, pericytes respond to inflammatory mediators such as CCL2 (monocyte chemoattractant protein‐1) and tumor necrosis factor‐α, in turn secreting CCL2, nitric oxide, and several cytokines. Pericytes can therefore act as promoters of both the innate and adaptive arms of the immune system. Much like professional phagocytes, pericytes also have the ability to clear up cellular debris and macromolecular plaques. Moreover, pericytes promote the activities of CNS glia, including in maturation of oligodendrocyte lineage cells for myelination. Conversely, pericytes can impair regenerative processes by contributing to scar formation. A better characterization of CNS pericytes and their functions would bode well for therapeutics aimed at alleviating their undesirable properties and enhancing their benefits.